Kinerja Keuangan dan Klasterisasi 8 Provinsi Maritim di Indonesia - Ardiansyah Ardiansyah; Diana Nurindrasari (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2024)
This research aims to examine the regional financial performance of maritime provinces that are members of the BKSDK as well as clustering financial performance based on 3 Indonesian regions, namely the Western Indonesia Region (WIB), the Central Indonesia Region (WITA), and the Eastern Indonesia Region (WIT). This research approach is quantitative using data from the 2022- 2023 Budget Realization Report (LRA) in 8 maritime provinces by calculating the regional independence ratio, harmony ratio, and growth ratio. The results of the research show that the overall average independence ratio of independent provinces is at a low to medium level, but the regional clusters have different levels. The overall average regional compatibility ratio and clustering have a good level of compatibility. Meanwhile, the growth ratio, both overall average and clustered has decreased.